2022
DOI: 10.1155/2022/7231046
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Relationship between Hub Genes and Immune Cell Infiltration in Vascular Endothelial Cells of Proliferative Diabetic Retinopathy Using Bioinformatics Methods

Abstract: Background. Diabetic retinopathy (DR) is a serious ophthalmopathy that causes blindness, especially in the proliferative stage. However, the pathogenesis of its effect on endothelial cells, especially its relationship with immune cell infiltration, remains unclear. Methods. The dataset GSE94019 was downloaded from the Gene Expression Omnibus (GEO) database to obtain DEGs. Through aggregate analyses such as Gene Ontology (GO) and Kyoto Encyclopedia of Gene and Genome (KEGG) pathway enrichment analysis, a protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Diabetic patients with PDR are more prone to proteinuria than diabetic patients without PDR, and the level of proteinuria is positively correlated with the severity of DR. It has also been confirmed 17 that PDR is a risk factor for diabetic nephropathy (DN), which in turn has a great predictive effect on PDR. Our results showed that the level of urinary albumin was an independent risk factor for the occurrence of PDR, which is in line with previous reports.…”
Section: Discussionmentioning
confidence: 92%
“…Diabetic patients with PDR are more prone to proteinuria than diabetic patients without PDR, and the level of proteinuria is positively correlated with the severity of DR. It has also been confirmed 17 that PDR is a risk factor for diabetic nephropathy (DN), which in turn has a great predictive effect on PDR. Our results showed that the level of urinary albumin was an independent risk factor for the occurrence of PDR, which is in line with previous reports.…”
Section: Discussionmentioning
confidence: 92%
“…Bioinformatics methods have been widely used for the exploration of key pathogenic factors and potential therapeutic targets in diabetic retinopathy (33)(34)(35). To the best of our knowledge, bioinformatics analysis of pyroptosis-related genes in diabetic retinopathy has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In blood T cells, EEF1A1 (ENSG00000156508) encodes the same type of alpha subunit of a complex, namely, elongation factor-1, which is responsible for aminoacyl tRNAase delivery to the ribosome; promotes cell growth and proliferation; and inhibits apoptosis (Mills and Gago, 2021). Huang et al found that the expression of EEF1A1 was positively correlated with the number of initial CD4 + T cells (Huang and Zhou, 2022), indicating that EEF1A1 may be associated with cellular immunity. In addition, EEF1A1 could inhibit viral growth (Zhang et al, 2015), and it is associated with inflammatory responses (Maruyama et al, 2007).…”
Section: Figure 10mentioning
confidence: 99%